Beta-Alanine Supplementation for CrossFit® Performance - Hannah Verity; Darren Candow; Philip D. Chilibeck (Nutraceuticals)
This study aimed to investigate whether beta-alanine supplementation (BA) improves performance and rating of perceived exertion (RPE) and reduces the respiratory exchange ratio (RER) during a CrossFit® workout. Fourteen participants were randomized in a double-blind design to either BA or placebo, with 12 participants (7 males, 5 females, 32 ± 9.2 y) completing the study. Participants performed two tests, separated by three weeks of supplementing with either 6.4 g/day of BA or placebo. Performance tests involved time to complete an adapted CrossFit® “Fran” Workout of the Day: 21-15-9 repetition scheme alternating between dumbbell thrusters and kipping pull-ups. No significant differences between the BA group and the placebo group were observed for performance time improvement (−13.4 s vs. −12.9 s, p = 0.97), change in mean RER (0.06 vs. 0.05, p = 0.84), or change in RPE (10-point scale) (−0.4 vs. −0.07, p = 0.56). There was a group × time × time during test interaction for RER (p = 0.021). Compared to pre-testing, post-testing RER was higher at the 25% time point of the test for the BA group and at the 75% and 100% time points in the placebo group (p < 0.05). Beta-alanine did not show significant ergogenic effects during an adapted version of the CrossFit® workout “Fran”, although it might have helped with the buffering of acidity later in the test, based on RER.